Antibacterial activity against pathogenic Vibrio and cytotoxicity on human hepatocyte of nano-silver prepared by polysaccharide-protein complexes - He, Peirong; Wang, Wenying; Jian, Wenjie (Frontiers in Microbiology, 2024)
Silver nanoparticles (AgNPs) are potential antibacterial agents against pathogenic Vibrio bacteria in the field of public health, yet their widespread use is limited by dispersibility and biocompatibility. In a previous study, highly dispersible AgNPs were fabricated using a polysaccharide–protein complex (PSP) obtained from the viscera of Haliotis discus. In this study, the antibacterial activity of PSP-AgNPs against pathogenic Vibrio and its cytotoxicity for human hepatocytes (LO2) was evaluated. At dosages of 3.125–25.0 μg/mL, PSP-AgNPs demonstrated excellent antibacterial activity against several pathogenic Vibrio strains (such as V. fluvialis, V. mimicus, V. hollisae, V. vulnificus, and V. furnissii), and no cytotoxicity on LO2 cells. This was evidenced by cellular viability, reactive oxygen species, and antioxidase activities. However, severe cytotoxicity was observed at a PSP-AgNPs concentration of 50.0 μg/mL. Furthermore, intracellular oxidative stress was the predominant mechanism of toxicity induced by PSP-AgNPs. Overall, PSP-AgNPs are highly biocompatible in the range of effective antibacterial dosages, identifying them as promising bactericide candidates in the field of public health.